Answer:
(f - g)(3) = 6
General Formulas and Concepts:
<u>Pre-Algebra</u>
- Order of Operations: BPEMDAS
<u>Algebra I</u>
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = 4x - 2
g(x) = x + 1
<u>Step 2: Find</u>
<em>Find (f - g)(x)</em>
- Substitute: (f - g)(x) = 4x - 2 - (x + 1)
- Distribute -1: (f - g)(x) = 4x - 2 - x - 1
- Combine like terms: (f - g)(x) = 3x - 3
<em>Find (f - g)(3)</em>
- Substitute: (f - g)(3) = 3(3) - 3
- Multiply: (f - g)(3) = 9 - 3
- Subtract: (f - g)(3) = 6
Answer:
c = 196
Step-by-step explanation:
To obtain a perfect square trinomial
Add ( half the coefficient of the x- term )² to x² + 28x
x² + 2(14)x + (14)², that is
x² + 28x + 196
= (x + 14)² ← a perfect square
Answer:
B
Step-by-step explanation:
I took the test and got it right
To find missing lengths of sides
hope this helped have a nice day